2005
DOI: 10.1038/sj.jhh.1001924
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertension and its relationship with obesity: results from a national blood pressure survey in Eritrea

Abstract: The prevalence of cardiovascular diseases has been shown to be on the increase in Africa based on hospital-based information and limited national surveys. A recent report on analysis of data from Health Information Management Systems (HIMS) highlighted an increasing burden of noncommunicable diseases (NCDs) in Eritrea, with the incidence of hypertension doubling in a space of 6 years. HMIS data are only a proxy of national prevalence rates, necessitating the conduct of national surveys. The WHO STEPwise approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
41
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 20 publications
20
41
9
1
Order By: Relevance
“…The prevalence of hypertension among the adolescents in this present study was 3.5%, and was consistent with the findings of other studies indicating that BP increases with age (11,36) . The implication of this observation is disturbing, granted that children who are obese are at greater risk for high BP at adulthood and the possibility of developing CVDs later in life.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The prevalence of hypertension among the adolescents in this present study was 3.5%, and was consistent with the findings of other studies indicating that BP increases with age (11,36) . The implication of this observation is disturbing, granted that children who are obese are at greater risk for high BP at adulthood and the possibility of developing CVDs later in life.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of hypertension found (29) , others almost similar values (13,30) , while a majority of the studies had disproportionately higher prevalence rates of hypertension (Table 5). (1,12,13,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) The likely reasons for the difference between the prevalence of hypertension in this study and those reported in the literature might be the use of different age groups, differing research methods and definitions of BP, as well as differences in reported prevalence and risk estimates. It is possible too, that geographical location may account for the difference in distribution of BP.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…A recent study by Mufunda et al, 14 also using the STEPwise approach in the same geographical area where this relationship was reported, described a related finding where blood pressure positively correlated to BMI only in the normal range of BMI but the relationship ceased to exist at low or very high BMI. Further increase/decrease in BMI did not result in increase/decrease in blood pressure, suggesting a saturating/threshold effect.…”
mentioning
confidence: 74%
“…Further increase/decrease in BMI did not result in increase/decrease in blood pressure, suggesting a saturating/threshold effect. 14 Research attention has simultaneously been targeted at identifying regional population BMI/blood pressure relationships and on understanding pathophysiological mechanisms that mediate this relationship. Longitudinal studies on tracking early childhood obesity into adult obesity have recognized a clear link between childhood obesity and increased cardiovascular morbidity in adulthood.…”
mentioning
confidence: 99%